A high-toughness flame-retardant drag chain cable and preparation method thereof
Through a multi-component composite system, combined with polyvinyl chloride resin, nitrile rubber, thermoplastic polyurethane elastomer and composite flame retardant, the outer sheath material of high-toughness flame retardant drag chain cable is formed, solving the difficulties in performance balance of existing materials and achieving a comprehensive improvement of high toughness, flame retardancy and oil resistance.
Patent Information
- Application Number
- CN202411766757.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-04
AI Technical Summary
While existing drag chain cable outer sheath materials are difficult to achieve high toughness, flame retardancy, oil resistance and easy processability in performance balance, the addition of traditional flame retardants will lead to a decrease in mechanical properties.
A multi-component composite system is adopted, including polyvinyl chloride resin, nitrile rubber, thermoplastic polyurethane elastomer and composite flame retardant. The functional components are organically combined through chemical bonds to form the outer sheathing material of the high-toughness flame retardant drag chain cable.
It achieves excellent flame retardant and oil resistance while maintaining high toughness, solves the difficulties of traditional materials in performance balance, and improves the overall performance and service life of the cable.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of drag chain cables, and in particular to a high-toughness flame-retardant drag chain cable and a preparation method thereof. Background Art
[0002] With the rapid development of industrial automation, intelligence and digitalization, the demand for high-end equipment such as high-end machine tools, industrial robots, and automated production lines is growing. As a key component for power and signal transmission in these devices, the importance of drag chain cables is becoming increasingly prominent, and their demand is also continuing to rise.
[0003] Drag chain cable, also known as towing cable or tank chain cable, is a highly flexible special cable that can be moved back and forth frequently without being easily worn. It is mainly used in industrial robots, CNC machine tools, automated production lines, packaging equipment, cranes, port machinery, wind power generation equipment and other scenes that require frequent movement or bending. The main features of the drag chain cable are high flexibility, high wear resistance and high fatigue resistance, which can maintain stable power and signal transmission in complex working environments.
[0004] From a structural point of view, drag chain cables are usually composed of conductors, insulation layers, fillers, shielding layers, inner sheaths, reinforcements and outer sheaths. Among them, the outer sheath, as the outermost protective layer, is in direct contact with the external environment and is the key part that determines the overall performance of the cable.
[0005] The use environment of drag chain cables is usually harsh, and they may face many challenges such as high temperature, low temperature, humidity, oil pollution, chemical corrosion, mechanical wear, etc. Therefore, drag chain cables need to have high flexibility and resilience, excellent wear resistance, good oil resistance and chemical resistance, excellent temperature resistance, appropriate flame retardancy, as well as tensile and torsion resistance.
[0006] At present, the commonly used materials for the outer sheath of drag chain cables are mainly the following:
[0007] 1. Polyvinyl chloride (PVC): low price, corrosion resistance and easy processing, but the heat resistance and oil resistance are not ideal, the heat deformation temperature is low, and the impact resistance is poor.
[0008] 2. Polyethylene (PE): It has good electrical properties and chemical stability, but its heat resistance and wear resistance are relatively poor.
[0009] 3. Polyurethane (PU): It has excellent wear resistance, oil resistance and mechanical properties, and a wide operating temperature range, but the addition of flame retardants may lead to a decrease in mechanical properties and processability.
[0010] 4. Thermoplastic Elastomer (TPE): It combines the advantages of plastics and rubber, with good flexibility and resilience, but its temperature resistance and oil resistance may not be as good as some special materials.
[0011] 5. Fluoroplastics: such as polytetrafluoroethylene (PTFE), have excellent chemical resistance and high temperature resistance, but are expensive and difficult to process.
[0012] As the application environment becomes increasingly harsh, a single material often cannot meet the comprehensive requirements of the outer sheath of the drag chain cable. Therefore, researchers have begun to try to improve the comprehensive performance of the outer sheath of the drag chain cable by compounding materials. For example, compounding PVC with other materials such as nitrile rubber (NBR) can improve the flexibility and oil resistance of the material while maintaining the good processability of PVC. For another example, adding flame retardants to PU can improve the flame retardant properties of the material.
[0013] CN115260673A discloses a soft high-strength flame-retardant PVC cable material for a drag chain cable and a preparation method thereof. The materials include: 50-100 parts of a PVC resin with a polymerization degree of 1300, 0-50 parts of a PVC resin with a polymerization degree of 2500, 10-20 parts of trioctyl trimellitate, 15-20 parts of a polyester plasticizer 2050, 4-8 parts of antimony trioxide, 6-10 parts of zinc borate, 4-8 parts of a filler, 8-16 parts of aluminum hydroxide, 8-12 parts of a calcium zinc heat stabilizer, 10-15 parts of a nitrile rubber P95, 10-15 parts of EVA (VA content 32%), 0.4-0.6 parts of a lubricant, 0.4-1 parts of a processing modifier P551J, 3-5 parts of an ethylene-vinyl acetate-maleic anhydride copolymer, 10-20 parts of a polyester elastomer, and 1-2 parts of an inorganic silicate clay.
[0014] However, when compounding materials, it is still a huge challenge to ensure the compatibility between the components while balancing high toughness, flame retardancy, oil resistance and processability. In particular, when adding flame retardants, the mechanical properties of the material often decrease, which is a serious problem for drag chain cables that need to be bent frequently.
[0015] Therefore, developing a drag chain cable outer sheath material that has high toughness, good flame retardancy, excellent oil resistance and easy processing is of great significance for improving the overall performance and service life of the drag chain cable. This is also the focus and difficulty of current industry research, and is also the key technical problem to be solved by the present invention. Summary of the invention
[0016] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a high-toughness flame-retardant drag chain cable and a preparation method thereof. The outer sheath material of the present invention not only maintains high toughness, but also has excellent flame retardant properties and oil resistance, which meets the use requirements of drag chain cables in frequent bending and complex working environments, and effectively solves the problem of traditional materials in performance balance.
[0017] In order to achieve the above object, the present invention adopts the following technical solution:
[0018] A high-toughness flame-retardant drag chain cable comprises an outer sheath, wherein the outer sheath material is made of the following components in parts by weight: 35-50 parts of polyvinyl chloride resin, 15-25 parts of nitrile rubber, 4-8 parts of thermoplastic polyurethane elastomer, 3-10 parts of composite flame retardant, 2-8 parts of silicon dioxide, 2-4 parts of stabilizer, 0.1-0.5 parts of lubricant, and 0.1-0.5 parts of antioxidant.
[0019] Preferably, the acrylonitrile content of the nitrile rubber is 32-35%; and the K value of the polyvinyl chloride resin is 60-65.
[0020] Preferably, the silica particle size is 5-60 μm.
[0021] Preferably, the stabilizer is a calcium zinc stabilizer; the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; and the lubricant is polyethylene wax or stearic acid.
[0022] Preferably, the preparation method of the composite flame retardant comprises the following steps:
[0023] (1) adding carbon fiber to anhydrous toluene, then dropwise adding 3-isocyanatepropyltrimethoxysilane, stirring under a nitrogen atmosphere, washing the product, and vacuum drying to obtain modified carbon fiber;
[0024] Surface modification of carbon fiber: 3-isocyanate propyl trimethoxysilane reacts with the hydroxyl group (-OH) on the surface of carbon fiber. The methoxy group (-OCH 3 ) condenses with the hydroxyl groups on the carbon fiber surface to form Si-OC bonds and introduce active isocyanate groups (-NCO) on the carbon fiber surface. 3 O) 3 Si-(CH 2 ) 3 -NCO → CF-O-Si-(CH 2 ) 3 -NCO + 3CH 3 OH (CF stands for carbon fiber).
[0025] Preferably, in step (1), the usage ratio of carbon fiber, anhydrous toluene and 3-isocyanatepropyltrimethoxysilane is 10 g:50 mL:0.2-1 g.
[0026] Preferably, in step (1), the stirring condition is 50-80° C. for 2-12 h.
[0027] Preferably, in step (1), the carbon fiber is PAN-based carbon fiber T300, with a diameter of 6.91 μm and a length of 1 to 3 mm.
[0028] (2) Add 2-carboxyethylphenylphosphorous acid and aminopyrazine to DMF, then add EDC·HCl, stir and react under nitrogen atmosphere, and purify the product to obtain an intermediate;
[0029] Synthesis of intermediates: The carboxyl group (-COOH) of 2-carboxyethylphenylphosphite reacts with the amino group (-NH 2 ) undergoes a condensation reaction under the catalysis of EDC·HCl to form intermediates containing phosphorus and nitrogen, mainly generating amide bonds (-CONH-). Reaction formula: R-COOH + H 2 N-Py + EDC·HCl → R-CONH-Py + H 2 O (R represents 2-carboxyethylphenylphosphinoic acid main body, Py represents pyrazine ring).
[0030] Preferably, in step (2), the usage ratio of 2-carboxyethylphenylphosphite, aminopyrazine and EDC·HCl is 1-2 g: 0.8-1.6 g: 0.1-0.3 g; and the stirring reaction conditions are 80-110° C. and the stirring reaction is performed for 6-16 h.
[0031] Preferably, in step (2), the purification conditions are as follows: cooling the product to room temperature, pouring it into ice water and stirring it, extracting it with ethyl acetate, combining the organic phases, drying it with anhydrous sodium sulfate, filtering it and evaporating the solvent to obtain a crude product, then recrystallizing it with ethanol, collecting the crystals and drying them in vacuo.
[0032] (3) Adding the modified carbon fiber and the intermediate into anhydrous tetrahydrofuran, and then adding dibutyltin dilaurate, stirring the mixture under a nitrogen atmosphere to react, filtering, washing, and drying the product to obtain a composite flame retardant.
[0033] Synthesis of composite flame retardant: The isocyanate group (-NCO) on the surface of modified carbon fiber reacts with the hydroxyl group (-OH, from the hypophosphorous acid group) on the intermediate under the catalysis of dibutyltin dilaurate (DBTDL) to form a carbamate bond (-NHCOO-), which covalently connects the phosphorus and nitrogen-containing flame retardant components to the carbon fiber surface. Reaction formula: CF-O-Si-(CH 2 ) 3-NCO +HO-R-CONH-Py → CF-O-Si-(CH 2 ) 3 -NHCOO-R-CONH-Py.
[0034] Preferably, in step (3), the usage ratio of modified carbon fiber, intermediate and dibutyltin dilaurate is 10g:1-3g:0.01-0.1g.
[0035] Preferably, in step (3), the stirring reaction conditions are 50-65° C. for 4-12 h.
[0036] The present invention also claims protection for a method for preparing the high-toughness flame-retardant drag chain cable, and the method for preparing the outer sheath material comprises the following steps: uniformly stirring polyvinyl chloride resin, nitrile rubber, and thermoplastic polyurethane elastomer to obtain a resin mixture; uniformly mixing a stabilizer, a lubricant, an antioxidant, and a composite flame retardant, stirring for 6 to 12 minutes at 130 to 140°C and 5000 to 8000 r / min, and then adding silica and the resin mixture, stirring for 3 to 6 minutes at 2000 to 4000 r / min, cooling, extruding, granulating, and molding to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The present invention provides a high-toughness flame-retardant drag chain cable. Polyvinyl chloride resin is used as a base material, which not only provides good processability and cost-effectiveness, but also has excellent electrical insulation performance and weather resistance. Its K value is 60~65, ensuring appropriate molecular weight and mechanical strength. The addition of nitrile rubber significantly improves the flexibility, oil resistance and fatigue resistance of the material, especially its 32~35% acrylonitrile content ensures excellent oil resistance and improves the flexibility of the material in low temperature environment. Thermoplastic polyurethane elastomer further enhances the elasticity and wear resistance of the material, and improves the service life of the cable under frequent bending and friction conditions. The introduction of composite flame retardant not only effectively improves the flame retardant properties of the material, but also enhances the mechanical strength of the material through its special structure, solving the problem that traditional flame retardants may cause a decrease in mechanical properties. Other auxiliary raw materials such as silica are used as reinforcing fillers to improve the tensile strength and wear resistance of the material; stabilizers improve the thermal stability of the material; lubricants optimize processing fluidity; antioxidants enhance the anti-aging properties of the material. This multi-component composite system not only meets the use requirements of the drag chain cable in frequent bending and complex working environments, but also ensures the long-term reliability and safety of the cable. In particular, the outer sheath material of the present invention has excellent flame retardant and oil resistance while maintaining high toughness, providing a new technical solution for the development of high-performance drag chain cables and effectively solving the problem of traditional materials in terms of performance balance.
[0039] 2. The present invention provides a method for preparing a composite flame retardant. First, the surface of carbon fiber is modified by 3-isocyanate propyl trimethoxy silane. In this step, the methoxy group (-OCH 3 ) reacts with the hydroxyl group (-OH) on the surface of the carbon fiber to form a Si-OC bond, and at the same time introduces an active isocyanate group (-NCO) on the surface of the carbon fiber. This process significantly increases the surface activity of the carbon fiber and lays the foundation for subsequent reactions. Secondly, 2-carboxyethylphenyl hypophosphorous acid is reacted with aminopyrazine to synthesize a phosphorus- and nitrogen-containing intermediate. In this step, the carboxyl group (-COOH) of 2-carboxyethylphenyl hypophosphorous acid reacts with the amino group (-NH 2 ) undergoes a condensation reaction under the catalysis of EDC·HCl to form an amide bond (-CONH-). This reaction not only introduces phosphorus- and nitrogen-containing flame retardant elements, but also retains the activity of the hypophosphorous acid group, providing a reaction site for the formation of the final composite. Finally, the modified carbon fiber and the intermediate are reacted under the catalysis of dibutyltin dilaurate to obtain the final composite flame retardant. In this step, the isocyanate group (-NCO) on the surface of the modified carbon fiber reacts with the hydroxyl group (from the hypophosphorous acid group) on the intermediate to form a carbamate bond (-NHCOO-). Carbon fiber, phosphorus- and nitrogen-containing compounds are combined together through chemical bonds to form a new type of multifunctional composite flame retardant.
[0040] 3. The present invention provides a composite flame retardant. First, the surface of the carbon fiber is treated with a silane coupling agent, which significantly improves the surface activity and reactivity of the carbon fiber. The modified carbon fiber not only has a larger specific surface area, but also forms a stronger interface bond with the resin matrix. This improved interface property is conducive to the effective transmission of stress, thereby improving the overall strength and toughness of the outer sheath material. In addition, a special molecular structure is formed on the surface of the modified carbon fiber, which can be quickly converted into a stable carbon layer under high temperature conditions. This carbon layer has a unique porous structure and can effectively block the transfer of heat and oxygen. Secondly, by introducing a phosphorus-containing compound through 2-carboxyethylphenyl hypophosphorous acid, the present invention further enhances the flame retardant properties of the material. This phosphorus-containing structure can promote the formation of a dense phosphate carbon layer during the combustion process, effectively inhibiting the continuation of combustion. At the same time, the aromatic structure in this compound not only improves the thermal stability of the material, but also increases the rigidity of the resin matrix, thereby improving the overall mechanical properties of the outer sheath material. The presence of the aromatic ring can also increase the free volume between molecules. This characteristic helps to improve the impact resistance and overall toughness of the material, which is particularly important for drag chain cables that are often under dynamic loads. Finally, the introduction of the nitrogen-containing cyclic compound aminopyrazine brings a synergistic effect to the flame retardant system. This structure can not only synergize with the aforementioned phosphorus-containing compounds to promote the formation of a more effective expanded carbon layer, but also release non-flammable gases during the combustion process, jointly inhibiting the combustion process from both the gas phase and the condensed phase. This multiple flame retardant mechanism significantly improves the overall flame retardant properties of the sheath material. From a holistic perspective, the new composite flame retardant provided by the present invention organically combines the functional components through chemical bonds, overcomes the shortcomings of easy migration and easy precipitation of traditional physical mixed flame retardants, and ensures the long-term stability of the flame retardant effect. At the same time, due to the use of readily available raw materials and relatively simple synthetic routes, the method has good practicality and economy. This composite flame retardant not only significantly improves the flame retardant properties of the material, but also enhances its mechanical strength and toughness, while maintaining good processability. It provides a new idea for solving the difficult problem of balancing the flame retardant properties and mechanical properties of the outer sheath material of the high-performance drag chain cable, and opens up a new direction for technological innovation in related fields. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0042] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0043] The model of the thermoplastic polyurethane elastomer is selected from one or more of 1185A12WM, 1185A10WM, 1185A10M, 1175A10W, and 1185A10;
[0044] The carbon fiber was pretreated before use, placed at 60°C and dried for 30 minutes; immersed in 1 mol / L hydrochloric acid solution for 2 hours, taken out, washed with water, and dried.
[0045] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0046] (1) Add 10 g of carbon fiber to 50 mL of anhydrous toluene, then dropwise add 0.2-1 g of 3-isocyanatepropyltrimethoxysilane, stir and react at 50-80 °C in a nitrogen atmosphere for 2-12 h, wash the product, and vacuum dry to obtain modified carbon fiber;
[0047] (2) Add 1-2 g of 2-carboxyethylphenylphosphorous acid and 0.8-1.6 g of aminopyrazine to 50 mL of DMF, then add 0.1-0.3 g of EDC·HCl, and stir the reaction at 80-110°C in a nitrogen atmosphere for 6-16 h. Cool the product to room temperature, pour it into ice water, stir it, extract it with ethyl acetate, combine the organic phases, dry it with anhydrous sodium sulfate, filter and evaporate the solvent to obtain a crude product, then recrystallize it with ethanol, collect the crystals and dry them in vacuo to obtain an intermediate;
[0048] (3) Add 10 g of modified carbon fiber and 1-3 g of the intermediate into 50 mL of anhydrous tetrahydrofuran, then add 0.01-0.1 g of dibutyltin dilaurate, stir and react at 50-65 °C in a nitrogen atmosphere for 4-12 h, filter the product, wash with tetrahydrofuran, and dry to obtain a composite flame retardant;
[0049] (4) 35-50 parts of polyvinyl chloride resin, 15-25 parts of nitrile rubber, and 4-8 parts of thermoplastic polyurethane elastomer are mixed uniformly to obtain a resin mixture; 2-4 parts of stabilizer, 0.1-0.5 parts of lubricant, 0.1-0.5 parts of antioxidant, and 3-10 parts of composite flame retardant are mixed uniformly, and stirred at 130-140° C. and 5000-8000 r / min for 6-12 minutes, and then 2-8 parts of silica and the resin mixture are added, and stirred at 2000-4000 r / min for 3-6 minutes, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0050] The present invention will be further described below through specific embodiments.
[0051] Example 1
[0052] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0053] (1) 10 g of carbon fiber was added to 50 mL of anhydrous toluene, and then 1 g of 3-isocyanatepropyltrimethoxysilane was added dropwise. The mixture was stirred and reacted at 80 °C under a nitrogen atmosphere for 2 h. The product was washed and vacuum dried to obtain modified carbon fiber.
[0054] (2) 2 g of 2-carboxyethylphenylphosphorous acid and 1.6 g of aminopyrazine were added to 50 mL of DMF, followed by the addition of 0.3 g of EDC·HCl, and the reaction was stirred at 110°C for 6 h under a nitrogen atmosphere. The product was cooled to room temperature, poured into ice water, stirred, extracted with ethyl acetate, the organic phases were combined, dried over anhydrous sodium sulfate, filtered, and the solvent was evaporated to obtain a crude product, which was then recrystallized from ethanol, and the crystals were collected and dried in vacuo to obtain an intermediate;
[0055] (3) 10 g of modified carbon fiber and 3 g of the intermediate were added to 50 mL of anhydrous tetrahydrofuran, and then 0.1 g of dibutyltin dilaurate was added. The mixture was stirred and reacted at 65 °C in a nitrogen atmosphere for 4 h. The product was filtered, washed with tetrahydrofuran, and dried to obtain a composite flame retardant.
[0056] (4) 500 g of polyvinyl chloride resin, 250 g of nitrile rubber, and 80 g of thermoplastic polyurethane elastomer are stirred evenly to obtain a resin mixture; 40 g of calcium zinc stabilizer CZ-310, 5 g of lubricant stearic acid, 5 g of antioxidant, and 100 g of composite flame retardant are mixed evenly, stirred at 135° C. and 6000 r / min for 10 min, and then 80 g of silica and the resin mixture are added, stirred at 3000 r / min for 5 min, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0057] Example 2
[0058] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0059] (1) 10 g of carbon fiber was added to 50 mL of anhydrous toluene, and then 0.8 g of 3-isocyanatepropyltrimethoxysilane was added dropwise. The mixture was stirred and reacted at 70 °C under a nitrogen atmosphere for 6 h. The product was washed and vacuum dried to obtain modified carbon fiber.
[0060] (2) 1.5 g of 2-carboxyethylphenylphosphorous acid and 1.4 g of aminopyrazine were added to 50 mL of DMF, followed by the addition of 0.2 g of EDC·HCl, and the reaction was stirred at 100°C for 8 h under a nitrogen atmosphere. The product was cooled to room temperature, poured into ice water, stirred, extracted with ethyl acetate, the organic phases were combined, dried over anhydrous sodium sulfate, filtered, and the solvent was evaporated to obtain a crude product, which was then recrystallized from ethanol, and the crystals were collected and dried in vacuo to obtain an intermediate;
[0061] (3) 10 g of modified carbon fiber and 2 g of the intermediate were added to 50 mL of anhydrous tetrahydrofuran, and then 0.08 g of dibutyltin dilaurate was added. The mixture was stirred and reacted at 60 °C in a nitrogen atmosphere for 8 h. The product was filtered, washed with tetrahydrofuran, and dried to obtain a composite flame retardant.
[0062] (4) 450 g of polyvinyl chloride resin, 200 g of nitrile rubber, and 60 g of thermoplastic polyurethane elastomer are stirred evenly to obtain a resin mixture; 30 g of calcium zinc stabilizer CZ-310, 1-5 g of lubricant stearic acid, 4 g of antioxidant, and 80 g of composite flame retardant are mixed evenly, stirred at 135 ° C and 6000 r / min for 10 min, and then 60 g of silica and the resin mixture are added, stirred at 3000 r / min for 5 min, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0063] Example 3
[0064] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0065] (1) 10 g of carbon fiber was added to 50 mL of anhydrous toluene, and then 0.5 g of 3-isocyanatepropyltrimethoxysilane was added dropwise. The mixture was stirred and reacted at 60 °C under a nitrogen atmosphere for 8 h. The product was washed and vacuum dried to obtain modified carbon fiber.
[0066] (2) 1.5 g of 2-carboxyethylphenylphosphorous acid and 1.2 g of aminopyrazine were added to 50 mL of DMF, followed by the addition of 0.2 g of EDC·HCl, and the reaction was stirred at 90°C under a nitrogen atmosphere for 12 h. The product was cooled to room temperature, poured into ice water, stirred, extracted with ethyl acetate, the organic phases were combined, dried over anhydrous sodium sulfate, filtered, and the solvent was evaporated to obtain a crude product, which was then recrystallized from ethanol, and the crystals were collected and dried in vacuo to obtain an intermediate;
[0067] (3) 10 g of modified carbon fiber and 2 g of the intermediate were added to 50 mL of anhydrous tetrahydrofuran, and then 0.05 g of dibutyltin dilaurate was added. The mixture was stirred and reacted at 55 °C under a nitrogen atmosphere for 8 h. The product was filtered, washed with tetrahydrofuran, and dried to obtain a composite flame retardant.
[0068] (4) 400 g of polyvinyl chloride resin, 200 g of nitrile rubber, and 50 g of thermoplastic polyurethane elastomer are stirred evenly to obtain a resin mixture; 30 g of calcium zinc stabilizer CZ-310, 3 g of lubricant stearic acid, 3 g of antioxidant, and 50 g of composite flame retardant are mixed evenly, stirred at 135° C. and 6000 r / min for 10 min, and then 40 g of silica and the resin mixture are added, stirred at 3000 r / min for 5 min, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0069] Example 4
[0070] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0071] (1) 10 g of carbon fiber was added to 50 mL of anhydrous toluene, and then 0.2 g of 3-isocyanatepropyltrimethoxysilane was added dropwise. The mixture was stirred and reacted at 50 °C under a nitrogen atmosphere for 12 h. The product was washed and vacuum dried to obtain modified carbon fiber.
[0072] (2) 1 g of 2-carboxyethylphenylphosphorous acid and 0.8 g of aminopyrazine were added to 50 mL of DMF, followed by the addition of 0.1 g of EDC·HCl, and the reaction was stirred at 80°C under a nitrogen atmosphere for 16 h. The product was cooled to room temperature, poured into ice water, stirred, extracted with ethyl acetate, the organic phases were combined, dried over anhydrous sodium sulfate, filtered, and the solvent was evaporated to obtain a crude product, which was then recrystallized from ethanol, and the crystals were collected and dried in vacuo to obtain an intermediate;
[0073] (3) Add 10 g of modified carbon fiber and 1 g of the intermediate into 50 mL of anhydrous tetrahydrofuran, then add 0.01 g of dibutyltin dilaurate, stir and react for 12 h at 50 °C under a nitrogen atmosphere, filter the product, wash with tetrahydrofuran, and dry to obtain a composite flame retardant;
[0074] (4) 350 g of polyvinyl chloride resin, 150 g of nitrile rubber, and 40 g of thermoplastic polyurethane elastomer are stirred evenly to obtain a resin mixture; 20 g of calcium zinc stabilizer CZ-310, 1 g of lubricant stearic acid, 1 g of antioxidant, and 30 g of composite flame retardant are mixed evenly, stirred at 135° C. and 6000 r / min for 10 min, and then 20 g of silica and the resin mixture are added, stirred at 3000 r / min for 5 min, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0075] Comparative Example 1
[0076] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0077] (1) 10 g of carbon fiber was added to 50 mL of anhydrous toluene, and then 1 g of 3-isocyanatepropyltrimethoxysilane was added dropwise. The mixture was stirred and reacted at 80 °C under a nitrogen atmosphere for 2 h. The product was washed and vacuum dried to obtain modified carbon fiber.
[0078] (2) 500 g of polyvinyl chloride resin, 250 g of nitrile rubber, and 80 g of thermoplastic polyurethane elastomer are stirred evenly to obtain a resin mixture; 40 g of calcium zinc stabilizer CZ-310, 5 g of lubricant stearic acid, 5 g of antioxidant, and 100 g of modified carbon fiber are mixed evenly, stirred at 135° C. and 6000 r / min for 10 min, and then 80 g of silica and the resin mixture are added, stirred at 3000 r / min for 5 min, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0079] Comparative Example 2
[0080] A method for preparing a high-toughness flame-retardant drag chain cable outer sheath material comprises the following steps:
[0081] (1) 2 g of 2-carboxyethylphenylphosphorous acid and 1.6 g of aminopyrazine were added to 50 mL of DMF, followed by the addition of 0.3 g of EDC·HCl, and the reaction was stirred at 110°C under a nitrogen atmosphere for 6 h. The product was cooled to room temperature, poured into ice water, stirred, extracted with ethyl acetate, the organic phases were combined, dried over anhydrous sodium sulfate, filtered, and the solvent was evaporated to obtain a crude product, which was then recrystallized from ethanol, and the crystals were collected and dried in vacuo to obtain an intermediate;
[0082] (2) 500 g of polyvinyl chloride resin, 250 g of nitrile rubber, and 80 g of thermoplastic polyurethane elastomer are stirred evenly to obtain a resin mixture; 40 g of calcium zinc stabilizer CZ-310, 5 g of lubricant stearic acid, 5 g of antioxidant, and 100 g of intermediate are mixed evenly, stirred at 135° C. and 6000 r / min for 10 min, and then 80 g of silica and the resin mixture are added, stirred at 3000 r / min for 5 min, cooled, extruded, granulated, and molded to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
[0083] The outer sheath materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests, and the tensile strength and elongation at break of the outer sheath materials were tested with reference to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the melt index was detected by using the MF-20 melt index meter produced by Instron (Shanghai) Testing Equipment Trading Co., Ltd., and the detection environment was: temperature 190°C, load 5kg; the vertical burning grade was tested with reference to GB / T 2408-2021 "Determination of combustion performance of plastics by horizontal and vertical methods"; the limiting oxygen index was tested with reference to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test"; the oil resistance was tested with reference to ISO 1817-2015, and the specimen was a cylinder with a diameter of 16 mm and a thickness of 4 mm, immersed in 100°C 20# engine oil for 100 h, and the volume change rate was recorded; the specific data are shown in Table 1.
[0084] Table 1 Test results of outer sheath material performance
[0085]
[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-toughness flame-retardant drag chain cable, characterized in that: It comprises an outer sheath, wherein the outer sheath material is made of the following components by weight: 35-50 parts of polyvinyl chloride resin, 15-25 parts of nitrile rubber, 4-8 parts of thermoplastic polyurethane elastomer, 3-10 parts of composite flame retardant, 2-8 parts of silicon dioxide, 2-4 parts of stabilizer, 0.1-0.5 parts of lubricant, and 0.1-0.5 parts of antioxidant; The preparation method of the composite flame retardant comprises the following steps: (1) adding carbon fiber to anhydrous toluene, then dropwise adding 3-isocyanatepropyltrimethoxysilane, stirring under a nitrogen atmosphere, washing the product, and vacuum drying to obtain modified carbon fiber; (2) Add 2-carboxyethylphenylphosphorous acid and aminopyrazine to DMF, then add EDC·HCl, stir and react under nitrogen atmosphere, and purify the product to obtain an intermediate; (3) Adding the modified carbon fiber and the intermediate into anhydrous tetrahydrofuran, and then adding dibutyltin dilaurate, stirring the mixture under a nitrogen atmosphere to react, filtering, washing, and drying the product to obtain a composite flame retardant.
2. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: The acrylonitrile content of the nitrile rubber is 32-35%; the K value of the polyvinyl chloride resin is 60-65.
3. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: In step (1), the usage ratio of carbon fiber, anhydrous toluene and 3-isocyanate propyltrimethoxysilane is 10 g:50 mL:0.2~1 g.
4. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: In step (1), the stirring condition is 50-80° C. for 2-12 h.
5. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: In step (2), the amount ratio of 2-carboxyethylphenylphosphorous acid, aminopyrazine and EDC·HCl is 1-2 g: 0.8-1.6 g: 0.1-0.3 g; and the stirring reaction conditions are 80-110° C. and the stirring reaction is carried out for 6-16 hours.
6. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: In step (2), the purification conditions are as follows: cooling the product to room temperature, pouring it into ice water and stirring it, extracting it with ethyl acetate, combining the organic phases, drying it with anhydrous sodium sulfate, filtering it and evaporating the solvent to obtain a crude product, then recrystallizing it with ethanol, collecting the crystals and drying them in vacuo.
7. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: In step (3), the usage ratio of modified carbon fiber, intermediate and dibutyltin dilaurate is 10g:1~3g:0.01~0.1g.
8. The high-toughness flame-retardant drag chain cable according to claim 1, characterized in that: In step (3), the stirring reaction conditions are 50-65° C. for 4-12 h.
9. A method for preparing a high-toughness flame-retardant drag chain cable according to any one of claims 1 to 8, characterized in that: The preparation method of the outer sheath material comprises the following steps: uniformly stirring polyvinyl chloride resin, nitrile rubber and thermoplastic polyurethane elastomer to obtain a resin mixture; uniformly mixing a stabilizer, a lubricant, an antioxidant and a composite flame retardant, stirring for 6 to 12 minutes at 130 to 140° C. and 5000 to 8000 r / min, then adding silicon dioxide and the resin mixture, stirring for 3 to 6 minutes at 2000 to 4000 r / min, cooling, extruding, granulating and molding to obtain the outer sheath material of the high-toughness flame-retardant drag chain cable.
Citation Information
Patent Citations
Flexible high-strength flame-retardant PVC (polyvinyl chloride) cable material for drag chain cable and preparation method thereof
CN115260673A
Nitrogen-containing aryl hypophosphorous acid metal salt and preparation method thereof
CN101792463A
Wear-resistant drag chain PVC modified material of and preparation method of PVC modified material
CN109337241A